Changing Political Preferences Among Dalits in Uttar Pradesh in the 2000s: Shift from Social Justice to Aspiration. Issue 1 (June 2019) - Pai, Sudha
Abstract: During the 2000s, political preferences among Dalits in Uttar Pradesh (UP) have undergone significant transformation. The decade has witnessed weakening of identity politics and simultaneously revival of the BJP. Against this backdrop, the article argues that Dalit politics in UP has entered a phase marked by internal fragmentation, uncertainty and a more complex character. Two rapid shifts are visible in their political preferences: from the BSP towards the BJP in the 2014 elections; second, from late 2015, violent protests by Dalits signalling their anger and disillusionment with the BJP. Two developments are responsible for these swift changes: rising economic aspirations among Dalits, a new all-India consciousness and leaders, impacted by the twin forces of globalisation and cultural modernisation. Second, the revival of the BJP under a new leadership that deftly wove together a strategy of promise of social inclusion and rapid economic development, which attracted Dalits, but which the BJP has failed to fulfil. The article points to unravelling of this new social coalition and concludes that the mere politics of symbolism may not help BJP obtain Dalit support in the 2019 elections.